Flame spray pyrolysis synthesis and H2S sensing properties of CuO-doped SnO2 nanoparticles - Chen, Zhicheng; Xu, Zuwei; Zhao, Haibo (Proceedings of the Combustion Institute, 2021)
In this work, CuO-doped SnO2 (CuO/SnO2) nanoparticles with different CuO mass fractions (0–1.0 wt%) are synthesized by a flame spray pyrolysis (FSP) route and applied to fabricate thin-film gas sensors for H2S detecting. The nanoparticles are characterized by X-ray diffraction (XRD), N2-physisorption isotherms, transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). Within the 0–1.0 wt% CuO-doping concentrations, all of the nanoparticles predominantly exhibit a spherical structure with a diameter of 5–15 nm, and possess a quite large specific surface area (110–125 m2/g). These textural characterizations suggest that Cu atoms form substitution doping in polycrystalline SnO2 nanoparticles at low CuO levels (< 0.5 wt%), and they are segregated as CuO nanoclusters at high CuO concentrations (0.5–1.0 wt%). From gas-sensing measurements, the CuO doping significantly improves the H2S sensing performance of SnO2 nanoparticles, especially at the optimal CuO-doping mass fraction of 0.5 wt%. The optimal CuO-doped SnO2 gas sensor exhibits a highest response (Ra/Rg = 1056) under a condition of 10 ppm H2S atmosphere at 125 °C. This is probably because a large number of highly dispersed small CuO nanoclusters are supported on the surface of the nanoparticle for 0.5 wt% doping, forming abundant p-n junctions with SnO2. When the CuO/SnO2 composite is exposed to H2S, semiconducting CuO is converted to metallic-like CuS, thereby increasing electrical conductivity and resulting in a high response. In addition, the optimal sensor displays good cycle performance and high H2S selectivity against other toxic and flammable gases including NH3, H2 and CO. Therefore, the gas sensor of 0.5 wt% CuO-doped SnO2 made by the FSP shows a large potential for H2S detecting in practical industrial application.